The Lived experience of divorced women with unexpected divorces: A qualitative study - Shafeinia, Azam; Farzad, Valiollah; Hosseinian, Simin; Abolmaali Alhosseini, Khadijeh (Applied Family Therapy Journal (AFTJ), 2021)
Aim: This study aimed to demonstrate the lived experience of divorced women with unexpected divorces. Methods: The present study explored and identified the process of occurrence of unexpected divorces with a qualitative approach based on phenomenological theory and the technique of semi-structured and problem-oriented interviews. The study population included women with unexpected and unilateral divorce who were living in Tehran. And ten women who experienced unexpected divorce were selected by purposive sampling method. These individuals were scrutinized deeply by using semi-structured interviews. The data foundation approach was used to describe and analyze the data. Results: After interviewing divorced women and analyzing and extracting data, there were 162 initial codes, 11 sub-themes, and 4 main themes. The main theme of marriage included a lifelong commitment, two sub-themes of the belief in the continuity and stability of marriage, and the belief in having a good life but facing the worst events. The second main theme, which is the changes of relationship from best friend to a perfect stranger, also included five sub-themes of sudden and unexpected termination, the duality of messages and psychological games, failure of assumptions, betrayal, and the role of problems and main family in the divorce of the study participants. The emotional processes participants during unexpected divorce as their third main theme had two sub-themes of emotional reactions to abandonment and the damages of an unexpected divorce. And the fourth and last main theme was reconstructing the life and dealing with a divorce that included two sub-themes of efficient methods of dealing with divorce and inefficient methods of dealing with it. Conclusions: The divorce experience among women implies being under the circumstance of individual and social vulnerabilities and the occurrence of various consequences that lead them to take advantage of protection mechanisms such as religion, secrecy, and trying to adapt to new conditions and reduce psychological, social and sexual harm. This issue, therefore, indicates their need to be understood and completely supported. These results provide a new perspective to the health group and society to truly understand the problems of divorced women in today’s world.